PROCESSES AND PROBLEMS OF HUMAN POTENTIAL FORMATION - I. A. Brusakova; V. I. Fomin (Дискурс)
The main problems of the description of human, social, manpower recourses are presented when managing enterprise to ensure enterprise competitiveness, key indicators of manpower efficiency are given, the concept of the human capital is revealed, the structure of the human capital is given. It is proposed to count the value of human potential depending on a physical condition of a person, not only in value terms. It is shown that the physical condition of a person directly depends on his «genetic predisposition», skills, abilities, knowledge gained by a particular person during various periods of his life.